Cooperative Astrocyte and Dendritic Spine Dynamics at Hippocampal Excitatory Synapses - Haber, Michael (J Neurosci, 2006)
Accumulating evidence is redefining the importance of neuron–glial interactions at synapses in the CNS. Astrocytes form “tripartite” complexes with presynaptic and postsynaptic structures and regulate synaptic transmission and plasticity. Despite our understanding of the importance of neuron–glial relationships in physiological contexts, little is known about the structural interplay between astrocytes and synapses. In the past, this has been difficult to explore because studies have been hampered by the lack of a system that preserves complex neuron–glial relationships observed in the brain. Here we present a system that can be used to characterize the intricate relationship between astrocytic processes and synaptic structures in situ using organotypic hippocampal slices, a preparation that retains the three-dimensional architecture of astrocyte–synapse interactions. Using time-lapse confocal imaging, we demonstrate that astrocytes can rapidly extend and retract fine processes to engage and disengage from motile postsynaptic dendritic spines. Surprisingly, astrocytic motility is, on average, higher than its dendritic spine counterparts and likely relies on actin-based cytoskeletal reorganization. Changes in astrocytic processes are typically coordinated with changes in spines, and astrocyte–spine interactions are stabilized at larger spines. Our results suggest that dynamic structural changes in astrocytes help control the degree of neuron–glial communication at hippocampal synapses.